If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(6x + -5y + 4) = 0 Reorder the terms: -1(4 + 6x + -5y) = 0 (4 * -1 + 6x * -1 + -5y * -1) = 0 (-4 + -6x + 5y) = 0 Solving -4 + -6x + 5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + -6x + 4 + 5y = 0 + 4 Reorder the terms: -4 + 4 + -6x + 5y = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -6x + 5y = 0 + 4 -6x + 5y = 0 + 4 Combine like terms: 0 + 4 = 4 -6x + 5y = 4 Add '-5y' to each side of the equation. -6x + 5y + -5y = 4 + -5y Combine like terms: 5y + -5y = 0 -6x + 0 = 4 + -5y -6x = 4 + -5y Divide each side by '-6'. x = -0.6666666667 + 0.8333333333y Simplifying x = -0.6666666667 + 0.8333333333y
| 5.1p-0.7(2+3p)=-10.4 | | 3/4y-6=1/4y+10 | | 28--4d=5d-17 | | 4+2(x-3)=20 | | 6x+6+2(9x-4)= | | 2b-3-10b-9= | | i(-i)= | | 0.25(8+4x)-0.5(10+2x)= | | 9w+w+8w= | | 3(x-1)+2(4x-5)=(x-3)+5 | | -2(7z+5)=-14z+13 | | 2sin^2x+3sinx+1=0 | | 3n^2-9n-3=0 | | -6w+19=8w+5 | | y+0.6y-1.2=2(y-1.4) | | -12x-14=-2(6x+7) | | h=-1+3l^2+s | | In(x-5)+In(x+6)=1 | | m^2+2mn-3n^2=0 | | X-3y=600 | | x^2+16x+64y^2=0 | | 5c+56=120 | | 9x+10=199 | | 128=3.14(8)(8)h | | 128=3.14(8)squaredh | | 3n+6-6=57-6 | | 44=w(2w-3) | | s=-.5gt+vt | | k^2-4k-24=0 | | Y=(9+4k)x | | 6+3y=-4 | | 2x^2+32x-64=0 |